Risk of cognition alteration and emotional frailty via circulating transcriptome in treatment naïve head and neck squamous cell cancer patients - Anusa, A.M. (J Oral Biol Craniofac Res, 2019)
BACKGROUND: There is a dearth of research examining the association between differential expression (DE) of genetic transcritome associated with cognition alteration (CA) and emotional frailty (EF) in treatment naïve head and neck squamous cell carcinoma (HNSCC) patients. The present study was undertaken to identify the DE of mRNA of CA-EF in HNSCC tumor and correlate with clinical and other known genetic factors that promote oncogenesis as well as CA-EF. MATERIAL AND METHODS: Using Genome-Wide Association Studies, putative genes associated with CA-EF(Prixie Fixie score ≥0.10) were identified. The DE of the mRNA of the thus selected genes were obtained from The CANCER GENOME ATLAS – HNSCC patients along with clinical details. The DE of mRNA pertaining to known factors such as inflammation, serotonergic and dopaminergic functions as well as clinical parameters were studied for association with the risk of DE of CA-EF. Appropriate statistics were performed and P ≤ 0.05 was taken as significant. RESULTS: A total of 520 HNSCC patients formed study group. There were 77 (14.81%) patients at risk for CD, 41 (7.9%) for CI and 113 (21.73%) for EF risk. In all, 103 (19.81%) HNSCC patients of this cohort had DE of mRNA of genes associated with CA. Inflammation, circadian genes, mTOR pathway, invasion and metastasis set of genes had a significant association with the risk of DE of CA-EF. DISCUSSION: Transcriptome's have been postulated to mediate CA-EF by targeted action on human brain. Differential Expression of putative genes associated with CA-EF have been demonstrated in HNSCC tumor. These DE could predispose the patients to CA-EF by the action of gene-environmental as well as psycho-social constructs. As CA-EF could adversely influence the treatment and alter the quality of life among survivors, screening for CA-EF at HNSCC presentation becomes imperative.